Anoxia y sus formas clínicas - Preciado Loaiza, Pedro David (Machala : Universidad Técnica de Machala, 2024)
Anoxia is defined as the near-total absence of oxygen in the tissues or organs of the human body, which can have various causes or origins. One of the most common causes is drowning, with figures exceeding 200,000 each year. Similarly, asphyxiation by hanging and strangulation also occurs, which helps to differentiate depending on the signs found for proper proceedings in the field of legal and forensic medicine. Objective: To analyze the concept of anoxia and its various forms, in order to differentiate each type according to its etiology and characteristics, through an exhaustive review of the current literature. Materials and Methods: A review of scientific articles from the last 5 years was conducted using ScienceDirect, PubMed, and Google Scholar. Conclusion: Anoxia is a condition that can vary greatly depending on its origin. Each of the forms it can take may lead to a different diagnosis and management of the situation, whether it is to manage a pathological state that the patient is experiencing or to assist forensic medicine in identifying the cause of death of an individual.
La anoxia tiene su definición como la ausencia casi total en los tejidos u órganos del cuerpo humano, la cual puede tener varias casusas o principios, siendo una de las más frecuentes por sumersión con cifras que superan los 200.000 cada año, por otro lado, tenemos del mismo modo asfixias por ahorcamiento y estrangulamiento, las cuales ayudan a diferenciar dependiendo de los signos que se encuentren para un buen proceder en el ámbito de la medicina legal y forense. Objetivo. - Analizar el concepto de anoxia y sus diversas formas, con el fin de diferenciar cada tipo según su etiología y características, mediante una revisión exhaustiva de la bibliografía actualizada. Materiales y Métodos: Se realizó una revisión de artículos científicos de los últimos 5 años en los buscadores ScienceDirect, PubMed y Google Académico. Conclusión: la anoxia es una condición que puede variar mucho dependiendo de como se origine, cada una de las formas en que se puede presentar puede llevar a un diagnostico y manejo distinto de la situación ya sea este para poder manejar un estado patológico que curse el paciente, o para ayudar a la medicina forense a identificar la causa de muerte de un individuo.
Keywords: ANOXIA; ANOXEMIA; HIPOXIA; ASFIXIA